Case Report: Unlocking opportunities in HER2-targeted antibody-drug conjugates for bulky leptomeningeal metastatic breast cancer - Leal, Alessandro; Kondziolka, Douglas; Pacione, Donato; Antwi, Stacy; Kurz, Sylvia; Lin, Nancy; Adams, Sylvia (Frontiers in Oncology, 2025)
Leptomeningeal carcinomatosis (LC) is a severe complication of metastatic breast cancer (mBC), with rising incidence. The prognosis for patients with LC has been poor, with a median overall survival of approximately four months. However, recent therapeutic advances, in particular the introduction of trastuzumab deruxtecan have dramatically changed the landscape of CNS metastases and improved outcomes. Here, we present the case of a 42-year-old woman with recurrent HER2+ breast cancer who developed extensive LC after multiple lines of treatment. Despite progressive disease, the patient exhibited a sustained response to trastuzumab deruxtecan, a novel antibody-drug conjugate (ADC), for 15 months, which was further extended by adding tucatinib. This case underscores the potential of ADCs, like trastuzumab deruxtecan, in controlling both brain metastases and leptomeningeal disease, offering hope for prolonged survival in patients with aggressive HER2+ mBC. Additionally, we highlight the evolving role of clinical trials, molecular profiling, and interdisciplinary care in managing this challenging condition. Ongoing trials continue to investigate new therapeutic options for HER2+ mBC with CNS involvement, promising to further improve outcomes and quality of life for patients facing this devastating disease.